Modulação autonômica cardíaca após exercícios com haste oscilatória em ambos os sexos - Cardoso, Marco Aurélio [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The aim of this study was to analyze the effects of exercise with oscillatory pole on cardiac autonomic modulation recovery in healthy women and men. In searches conducted in the main available databases it was not found similar studies. The exercise consisted of vibrating the pole with both hands held the oscillatory pole in the transverse plane, parallel to the ground; shoulder at 90 ° of flexion with the dominant side vibrating to the oscillatory pole in the sagittal plane perpendicular to the ground; shoulders with approximately 180 ° of flexion, both hands held the oscillatory pole vibrating to the frontal plane, parallel to the ground. Each position was performed for three sets of fifteen seconds. HRV was analyzed 10 minutes before exercise and post-exercise time: 0-5 minutes, 5-10 minutes, 10-15 minutes. The HRV indices were analyzed: SDNN (standard deviation of all normal RR intervals recorded in a time interval), RMSSD (square root of the square mean differences between adjacent normal RR intervals in a time interval), pNN50 (percentage of adjacent RR intervals lasting more difference than 50ms)...

O objetivo desta dissertação foi analisar os efeitos do exercício com haste oscilatória na recuperação da modulação autonômica cardíaca em mulheres e homens saudáveis. Em buscas realizadas nas principais bases de dados disponíveis não foi encontrado estudo semelhante. O protocolo de exercício consiste em vibrar a haste com ambas as mãos nos planos transversal, paralela ao solo; ombro a 90° de flexão do lado dominante vibrando-a a haste oscilatória no plano sagital perpendicular ao solo; com ombros a aproximadamente 180° de flexão, ambas as mãos seguraram a haste oscilatória vibrando-a no plano frontal, paralelo ao solo. Cada postura foi executada durante três séries de quinze segundos. A VFC Foi analisada 10 minutos antes do exercício e nos momentos pós-exercício: 0-5 minutos, 5-10 minutos, 10-15 minutos. Foram analisados os índices de VFC: SDNN (desvio padrão de todos os intervalos RR normais gravados em um intervalo de tempo), RMSSD (raiz quadrada da média do quadrado das diferenças entre intervalos RR normais adjacentes, em um intervalo de tempo), pNN50 (porcentagem dos intervalos RR adjacentes com diferença de duração maior que 50ms)...
Keywords: Fisioterapia; Sistema cardiovascular; Sistema nervoso autonomo; Batimento cardíaco; Physical therapy